Effect of confinement potential on exciton diamagnetism in the perspective of constituent carriers in a Quantum Well. (March 2018) - Vignesh, G.; Nithiananthi, P.
Abstract: Diamagnetic susceptibility of excitons is investigated in the perspective of the electron and hole separation along the lateral (ρ) and normal direction (z) of a GaAs/Alx Ga1-x As quantum well. Using a variational technique, the spatial extensions of these carriers has been observed. The coulomb interaction of the carriers is investigated by subjecting the carriers to three confinement potentials, Square (SQW), Parabolic (PQW) and Triangular Quantum Wells (TQW). The stability of the exciton has been estimated by observing the diamagnetic susceptibility. The hole is very sensitive to confinement potential and has tremendous variations in spatial extension. Among the three confinements, TQW offers more localization and high stability to excitons. The anisotropy of band parameters and the dielectric constants of the well and barrier materials are taken into consideration. Highlights: Effect of confinement potential on the spatial extension and diamagnetism of excitons. TQW offers good localization to excitons. Holes are highly sensitive to confinement potentials. Coulomb interaction of carriers can be estimated by diamagnetic susceptibility. Diamagnetic susceptibility of the exciton is a measure of the exciton size in nanostructures.